2020
DOI: 10.3390/mi11090794
|View full text |Cite
|
Sign up to set email alerts
|

The Spontaneous Imbibition of Micro/Nano Structures in Tight Matrix and the Influence on Imbibition Potential

Abstract: Tight matrix has relatively low permeability and porosity, with abundant micro/nano pores. The capillary force in these pores are relatively strong, making the wetting liquid easier to be imbibed in the matrix. This process is called spontaneous imbibition. The complexity of pore structure is identified as one of the key factors influencing the imbibition process, but the detailed mechanism is not clear. Thus, in this work, a method is proposed to evaluate the influence of pore structure on imbibition process.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The result implies that the sample with the TEO boundary condition had the largest diffusion ability, while TEC had the lowest diffusion ability. This nature of the curve was obtained by Li et al, where the diffusion ability was compared for different core samples. Higher diffusion ability depicts a greater gas displacement effect and improves production of gas.…”
Section: Resultsmentioning
confidence: 62%
See 3 more Smart Citations
“…The result implies that the sample with the TEO boundary condition had the largest diffusion ability, while TEC had the lowest diffusion ability. This nature of the curve was obtained by Li et al, where the diffusion ability was compared for different core samples. Higher diffusion ability depicts a greater gas displacement effect and improves production of gas.…”
Section: Resultsmentioning
confidence: 62%
“…Similar zones have also been observed elsewhere. , However, some variations in the imbibition profiles were observed because of the different boundary conditions. It is noteworthy that the direction of the core sample does not have any influence on the imbibition profile because the sample is fully immersed in water …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A soaking process, referring to an extended shut-in period, is commonly reported in shale gas wells after fracturing treatment. Theoretical and experimental studies have demonstrated that spontaneous imbibition (SI) plays an important role in the distribution of fracturing fluids during the soaking process (e.g., refs . Additionally, studies have demonstrated that imbibition during the soaking process can improve the production performance of shale gas wells. Consequently, studying the SI behaviors is of great significance to improve the understanding of gas recovery from shale reservoirs.…”
Section: Introductionmentioning
confidence: 99%